HAS2-Ezrin-ER axis plays a role in acquired antiestrogen resistance of ER-positive breast cancer - Sun, Xiaodan; Tang, Fen; Guo, Qian; Liu, Yiwen; He, Yiqing; Du, Yan; Gao, Feng; Zhang, Guoliang; Yang, Cuixia (Frontiers in Pharmacology, 2022)
The development of endocrine resistance is a major clinical problem in estrogen receptor-positive (ER+) breast cancer (BrCa) treatment, in which how cancer cells acquire resistance remains obscure. Hyaluronan synthase 2 (HAS2) is the most critical synthase in producing hyaluronan and is well known for its involvement in cancer growth, metabolism and metastasis. Recent evidence has proved that HAS2 is involved in cellular acquired resistance to drug therapy in BrCa. In this work, we first observed that HAS2 expression was decreased in the endocrine-resistant ER+ BrCa cells. Further knocking-out experiments confirmed that the loss of HAS2 in parental ER+ BrCa cells resulted in a following antiestrogen resistance. Next, we found that the HAS2-loss could induce an up-regulation of Ezrin, a member of the membrane cytoskeletal protein family who plays key roles in cellular signal transduction. Notably, we identified that the increase of Ezrin induced by HAS2-loss could inhibit the ERα expression and augment antiestrogen resistance, suggesting that a HAS2-Ezrin-ER axis may be associated with the acquirement of endocrine resistance in ER+ BrCa cells. Finally, knockdown or inhibition of Ezrin could restore the sensitivity of endocrine-resistant cells to antiestrogens treatment by activating ERα signaling. Taken together, our findings unraveled a novel HAS2-Ezrin-ER route in regulating the sensitivity of ER+ BrCa cells to antiestrogens, in which Ezrin may be a potential target in endocrine therapy.